Criminal Justice and Global Public Goods: The Prüm Forensic Biometric Cooperation Model. (October 2016) - Wilson, Tim J
This article places sharing forensic biometric data for international criminal justice cooperation purposes within the domain of global public goods. Such cooperation is a rational response to globalisation, but faces several obstacles. These range from sociocultural and political concerns about national legal and criminal justice autonomy to the potential impact of market fundamentalism on scientific standardisation and cooperation mechanism delivery. The significance of such inhibitors will vary as societal and personal perceptions of stability change. These issues are examined by analysing the progress achieved with the EU Prüm forensic biometric data exchange model. Shocks to European stability, such as the increased scale of terrorist crimes and the UK EU referendum result will inevitably test the resilience of Prüm. Combining insights from global public goods and criminal law scholarship, however, may help to identify how reactions to such shocks, including questions about future UK participation in Prüm, might be managed.